Nevermind, rather than adding the bottom equation they subtracted it which makes it come out to 2,3
subtract the 2nd equation from the 1st
you'll get 2x = 4
after solving you'll get x= 2
and put the value of x in any of the above eqn you'll get y
4x+3y=17
2x+3y=13
______________________________________________
4x+3y=17
(2x+3y=13) - multi ply by -2 to the x terms. Now add . . . .
4x + 3y = 17
-4x - 6y = -26
0 - 3y = -9
y =-9/-3 = 3
Next,
4x+3y=17
2x+3y=13, multiply by -1 to eliminate y terms,
4x +3y = 17
-2x - 3y = -13 then add,
?